Prevalence, Insidence and Progression Black-band Disease on Scleractinian Coral (Montipora spp) in Shallow Water of Pari Islands - Michael Delpopi; Neviaty Putri Zamani; Dedi Soedarma; Ofrie Johan (Marine Science Department Diponegoro University, 2015)
Black-band disease (BBD) is a persistent disease that cause the decline of the coral reef ecosystems, which is still slightly recorded in Indonesia, including in Pari Island, Thousand Islands. The objectives of this study were to determine progression, prevalence and incidence BBD on Montipora spp in shallow water of Pari Islands. Coral cover were estimated using line intercept transect (LIT) whereas the prevalence and incidence of BBD were carried out by using belt transect method with 1 m left and right of tape as long 20 m with 3 replications recorded approximately every two months. BBD progression was documented with a digital photograph method, the photograph of affected area of each coral was taken each day for 2 weeks. BBD was found to be spread in the surveyed area. The result show that prevalence and incidence of BBD showed a positive exponential relationship with water temperature. During the observation Both prevalence and incidence increased on May transitional season (wet-dry). The highest prevalence was found at 5,96 percent and whereas the maximum disease progression found at 0,46 cm/day.